The impact of supply chain quality management practices and knowledge transfer on organisational performance: an empirical investigation from China. Issue 3 (4th May 2018) - Hong, Jiangtao; Zhang, Yibin; Shi, Mingxia
ABSTRACT: In recent years, both quality management practices (QMP) and knowledge transfer (KT) have been studied extensively from inter-organisational and intra-organisational perspectives. However, to the best of our knowledge, the interaction between QMP and KT in a supply chain and their joint effects on organisational performance have not been addressed fully. The purpose of this paper is to provide insights for improving performance by mapping the relationship between supply chain quality management practices (SCQMP) and KT. A survey of 157 Chinese manufacturing firms is used to test a conceptual model that proposes relationship among SCQMP, KT and organisational performance (including operational performance and innovation performance). Structural equation modelling reveals that internal QMP have significantly positive effect on internal KT, while QMP at supply chain level have highly positive effect on cross-organisational KT. Furthermore, the results show that both internal KT and cross-organisational KT can promote operational and innovation performance, although the influence from internal KT is much more significant than cross-organisational KT for Chinese firms. The findings contribute to theory as well as practice by increasing understanding of how to improve the operational and innovation performance through enhancing SCQMP and KT.